Analysis of Neuron Specific Enolase Serum Levels in Traumatic Brain Injury - Yuliarni Syafrita; Nora Fitri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background : Traumatic brain injury is still the main cause of death and disability in productive age. Assessment the level of consciousness and imaging examinations after a brain injury can not always describe the severity of damage in the brain, this is because the pathological process is still ongoing due to secondary brain injury. Therefore, it is necessary to examine biomarkers that can describe the severity of the pathological process that occurs. The purpose of this study was to assess serum neuron-specific enolase (NSE) levels and their relationship to the severity and outcome of a traumatic brain injury. Methods : A cross sectional design was conducted in the emergency department of DR M Djamil Hospital, Padang. There were 72 patients who met the inclusion criteria. A Glasgow Coma Scale examination was performed to assess the severity of brain injury and examination of NSE serum levels at 48 hours post- injury using ELISA technique and assess the Glasgow outcome scale (GOS) at 6 weeks post-injury. Data analysis using SPSS 22 program, the results are significance if the p value <0.05 Results : The average NSE level was higher in severe brain injuries than moderate and mild brain injuries and this difference was statistically significant (p<0.05). The NSE serum levels were higher in poor outcomes than in good outcomes and this difference was statistically significant (p<0.05). Conclusion : High NSE serum levels in the acute phase were associated with the severity of the brain injury and poor outcome 6 weeks after the brain injury.